Electrochemical Behavior of PEDOT/Lignin in Ionic Liquid Electrolytes: Suitable Cathode/Electrolyte System for Sodium Batteries. Issue 8 (16th March 2017) - Casado, Nerea; Hilder, Matthias; Pozo‐Gonzalo, Cristina; Forsyth, Maria; Mecerreyes, David
Abstract: Biomass‐derived polymers, such as lignin, contain quinone/ hydroquinone redox moieties that can be used to store charge. Composites based on the biopolymer lignin and several conjugated polymers have shown good charge‐storage properties. However, their performance has been only studied in acidic aqueous media limiting their applications mainly to supercapacitors. Here, we show that PEDOT/lignin (PEDOT: poly(3, 4‐ethylenedioxythiophene)) biopolymers are electroactive in aprotic ionic liquids (ILs) and we move a step further by assembling sodium full cell batteries using PEDOT/lignin as electrode material and IL electrolytes. Thus, the electrochemical activity and cycling of PEDOT/lignin electrodes was investigated in 1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (BMPyrTFSI), 1‐butyl‐1‐methylpyrrolidinium bis(fluorosulfonyl)imide (BMPyrFSI), 1‐ethyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide (EMImTFSI) and 1‐ethyl‐3‐methylimidazolium bis(fluorosulfonyl)imide (EMImFSI) IL electrolytes. The effects of water and sodium salt addition to the ILs were investigated to obtain optimum electrolyte systems for sodium batteries. Finally, sodium batteries based on PEDOT/lignin cathode with imidazolium‐based IL electrolyte showed higher capacity values than pyrrolidinium ones, reaching 70 mAhg −1 . Our results demonstrate that PEDOT/lignin composites can serve as low cost and sustainable cathode materials for sodium batteries. Abstract : Sustai‐Na‐ble batteries : Electroacitivity of PEDOT/lignin (PEDOT: poly(3, 4‐ethylenedioxythiophene)) biopolymer is studied in aprotic ionic liquids, demonstrating an effective cathode/electrolyte system that is applied to develop sustainable sodium batteries. These results open up the possibility to use other lignin‐derived cathodes in sodium batteries as well as PEDOT/lignin in other electrochemical devices using ionic liquids as electrolytes.